Carbon–carbon coupling reactions catalyzed by supported Pd porphyrins. (19th March 2014) - Bagheri, Omid; Sadegh, Faranak; Moghadam, Majid; Tangestaninejad, Shahram; Mirkhani, Valiollah; Mohammadpoor‐Baltork, Iraj; Safiri, Mahsa
<x xml:space="preserve">Abstract</x> The tetrakis(4‐N‐methylpyridinium)porphyrinatopalladium(II) iodide, [Pd(TMPyP)]I4, supported on Dowex 50WX8 and Amberlite IR‐120 ion‐exchange resins, was used as heterogeneous, recyclable and active catalyst for the Suzuki–Miyaura and Heck cross‐coupling reactions. These catalysts were applied to coupling of various aryl halides with phenylboronic acid and styrene in Suzuki and Heck reactions, respectively, and the corresponding products were obtained in excellent yields and short reaction times. The catalysts could be recovered easily by simple filtration and reused several times without significant loss of their catalytic activity. The catalysts were characterized by diffuse‐reflectance UV–visible spectroscopy and scanning electron microscopy, and their stability was confirmed by TGA. Copyright © 2014 John Wiley & Sons, Ltd.